PENGARUH DUKUNGAN SUAMI TERHADAP PEMBERIAN IMUNISASI TETANUS TOXOID (TT) PADA IBU HAMIL DI BIDAN PRAKTEK MANDIRI (BPM) RESMIAH DI KECAMATAN TALAWI KABUPATEN BATUBARA TAHUN 2019 - Eliya Wardayani (Jurnal Education and Development, 2021)
The efforts to eliminated Maternal Tetanus and Neonatal (TMN) aimed at reducing the number of tetanus cases in maternal and neonatal to a level where TMN was no longer the primary concern of public health. Unlike polio or smallpox tetanus cannot eradicated, spores tetanus were in a worldwide environment, but though immunization of pregnant mother, women of childbearing age and the promotion of hygienic childbirth. The type of research used was analogous descriptive with cross sectional approach. The data used was primary with the instrument of this research was a questionnaire to know how a husband’s support affects though immunize against of toxoid tetanus. With 27 people who were pregnant and partners. Research conducted on an expectant husband shows that the average husband’s support for their wives not getting immunized groups were low as 9 people (53%). And in the group that gets the majority immunization of a husband’s support as high as 5 people (50%). Bivariate analysis using chi square test shows that a value of X2count > X2table of 3.148 > 1.234 means that Ho was being denied and that there was an effect of a husband’s support for tetanus toxoid immunization in the pregnant mother. It was recommended for husbands to search for information and actively find out everything related to health services for mother and child and support the wife in obtained health services that suit the mother’s needs.